ROMAN LAW LESSONS IN CONTEMPORARY LEGAL CONTEXTS: THE CREATION OF THE BASIC CHARACTERISTICS OF CONTEMPORARY CORPORATIONS IN MARKET ECONOMIES - Mucunski, Timcho; Klimovski, Aleksandar (University of Banja Luka, 2023)
In the scientific research of status law and the influence of law on socio-economic relations, the development of contemporary corporations stands out as an important issue. First, we must put into context the use of specific terms, i.e. whether to use “capital structures” or “corporations”. The reason being the fact that the Roman legal environment, as the key foundation for contemporary capital structures, did not recognise corporate entities the way they are received in today’s contemporary legal development. Henceforth, the authors will more often refer to contemporary terminology when explaining the developmental tendencies of contemporary corporate entities, with special attention on the analysis of the roadmap which lead from Roman law capital structures to contemporary, market-based, corporations.